Are environmental innovators persistent?. Issue 11 (19th September 2018) - Le Bas, Christian; Poussing, Nicolas
Abstract : A growing body of literature concerns innovation persistence, but does not deal with environmental innovation, which is an important topic in the context of global warming. In this paper, we contribute to this literature by testing whether environmental innovators are persistent. Our empirical approach rests on the use of the Community Innovation Survey (CIS) 2008 and CIS 2010 data for firms from Luxembourg. Due to the lack of harmonisation, we are obliged to carry out a consistent statistical retreatment related to the data. Our probit models show that environmental technological innovators are persistent. The phenomenon of environmental innovation persistence is also positively affected by regulation and voluntary measures.